Industrial Performance, Agglomeration, and Foreign Manufacturing Investment in the UK - Driffield, Nigel; Munday, Max (Journal of International Business Studies, 2000)
This paper examines the relationship between the comparative advantage of UK industries, and new inward investment into these industries. The paper demonstrates that the extent of foreign manufacturing investment in an industry, and the spatial agglomeration of that industry, are significant determinants of industry comparative advantage, thus providing evidence of agglomeration benefits to both domestic and foreign firms. The paper then shows that industry comparative advantage itself, together with a series of industry specific characteristics, are important determinants of new foreign manufacturing investment, thus providing evidence of the dynamic benefits of foreign direct investment in the UK economy.